2007
DOI: 10.1007/s00442-006-0655-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of global changes and extreme hydroclimatic events on macroinvertebrate community structures in the French Rhône River

Abstract: We assessed the temporal changes in and the relationships between the structures of the macroinvertebrate communities and the environmental conditions of the French Rhône River (the river from Lake Geneva to the Mediterranean Sea) over the last 20 years (1985-2004). Multisite environmental and biological datasets were analysed using multiple CO-inertia analysis (MCOA) and Procrustean analysis. Changes in environmental conditions were mainly marked by an improvement in water quality between 1985 and 1991 and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 61 publications
6
88
1
2
Order By: Relevance
“…A decrease in the resilience of macroinvertebrate communities affected by extreme hydroclimatic events was also observed in the Rhône river (Daufresne et al 2007). On a wider scale, increases of mean temperature and the frequency of heatwaves during the century predicted by different models (Beniston & Diaz 2004, EEA 2004, Schär et al 2004, Meehl & Tebaldi 2004 could result in the gradual disappearance of P. amnicum from the potamon and of V. piscinalis from the freshwater systems most directly exposed to climatic warming (Webb 1996), such as the Saône River.…”
Section: Recovery Possibilitiesmentioning
confidence: 74%
“…A decrease in the resilience of macroinvertebrate communities affected by extreme hydroclimatic events was also observed in the Rhône river (Daufresne et al 2007). On a wider scale, increases of mean temperature and the frequency of heatwaves during the century predicted by different models (Beniston & Diaz 2004, EEA 2004, Schär et al 2004, Meehl & Tebaldi 2004 could result in the gradual disappearance of P. amnicum from the potamon and of V. piscinalis from the freshwater systems most directly exposed to climatic warming (Webb 1996), such as the Saône River.…”
Section: Recovery Possibilitiesmentioning
confidence: 74%
“…Fish and invertebrate communities have been found to respond to increases in water temperature in the upper Rhône River in France (Daufresne et al, 2004(Daufresne et al, , 2007.…”
Section: Past Trendsmentioning
confidence: 99%
“…The study [11] observed influence of changes in environmental conditions on the change of macroinvertebrates in the river Rhone in France. It observed temporal change at the nine sites that were sampled from 1985 to 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Their results are very controversial. Some studies have shown community structure to be relatively stable, especially if environmental conditions do not vary over time [6], [7], [8], whereas others have reported considerable temporal changes in community structure [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%